2009
DOI: 10.1021/om9007604
|View full text |Cite
|
Sign up to set email alerts
|

A Rigidity-Modulated Approach toward the Construction of Metallacycles from a Flexible Tetratopic Ligand

Abstract: Conformation control of a flexible tetratopic ligand by modulation of the length of the rigid bridging ligand is achieved during the self-assembly of metallacycles. The ability to control the conformation of the flexible ligand using an ancillary rigid ligand provides a new method for the preparation of novel metallacycles that contain both flexible and rigid modules with highly accurate prediction of the final structures.Precise control of supramolecular metallacycles requires a rational design of molecular c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Compounds 24 and 25 were assembled by reacting a mixture of Re 2 (CO) 10 , TXyBim, and H 2 Bim or H 2 CA in toluene under solvothermal conditions in a one-step process (Scheme 12). 43 The coordination geometry around the Re centers in 24 and 25 is described as a distorted octahedral shape with a C 3 N 3 -, and C 3 NO 2 -donor environment, respectively, as evidenced by solid-state structures (Figure 10). The Re 3 3 3 Re distance in 25 is 8.141 Å, representing ∼2.9 Å longer than that found in 24.…”
Section: Other Metallacyclesmentioning
confidence: 99%
See 1 more Smart Citation
“…Compounds 24 and 25 were assembled by reacting a mixture of Re 2 (CO) 10 , TXyBim, and H 2 Bim or H 2 CA in toluene under solvothermal conditions in a one-step process (Scheme 12). 43 The coordination geometry around the Re centers in 24 and 25 is described as a distorted octahedral shape with a C 3 N 3 -, and C 3 NO 2 -donor environment, respectively, as evidenced by solid-state structures (Figure 10). The Re 3 3 3 Re distance in 25 is 8.141 Å, representing ∼2.9 Å longer than that found in 24.…”
Section: Other Metallacyclesmentioning
confidence: 99%
“…In another contribution from our laboratory, we reported that the rigid anionic linker responsible for determination of M···M separation allows for conformational control of the flexible motif with the simultaneous use of a short or long rigid bis(chelator), tetratopic flexible N-donors (1,2,4,5-tetrakis(5,6-dimethylbenzimidazol-1-ylmethyl)benzene, TXyBim), and fac -Re(CO) 3 cores during self-assembly (Scheme ). Compounds 24 and 25 were assembled by reacting a mixture of Re 2 (CO) 10 , TXyBim, and H 2 Bim or H 2 CA in toluene under solvothermal conditions in a one-step process (Scheme ) …”
Section: Other Metallacyclesmentioning
confidence: 99%
“…Complex 3 was air- and moisture-stable and sparingly soluble in polar organic solvents. Related N-donor-based SCC [(Re(CO) 3 ) 4 (CA) 2 (1,2,4,5-tetrakis(5,6-dimethylbenzimidazol-1-methyl)benzene)] is insoluble . The FT-IR spectrum of 3 confirms the presence of fac -Re(CO) 3 , CA 2– , PO, and P–OMe units.…”
mentioning
confidence: 96%
“…During the self-assembly process, the rigid anionic linker, which is responsible for determining M· · ·M separation, allows for conformational control of the flexible supramolecular entities [270]. The reaction of two different length rigid moieties such as 2,2 -bis(benzimidazolyl) (L52) and chloranilic acid (L133), with flexible ligand 1,2,4,5-tetrakis(5,6-dimethylbenzimidazol-1-ylmethyl)benzene (H 2 L137, TXyBim) and Re 2 (CO) 10 A single-crystal X-ray diffraction analysis showed that compounds 164 and 165 adopted a tetrametallic metallacyclic structure, in which the Re centers had a distorted octahedron with Scheme 65.…”
Section: Scheme 63mentioning
confidence: 99%
“…The reaction of two different length rigid moieties such as 2,2 -bis(benzimidazolyl) (L52) and chloranilic acid (L133), with flexible ligand 1,2,4,5-tetrakis(5,6-dimethylbenzimidazol-1-ylmethyl)benzene (H 2 L137, TXyBim) and Re 2 (CO) 10 A single-crystal X-ray diffraction analysis showed that compounds 164 and 165 adopted a tetrametallic metallacyclic structure, in which the Re centers had a distorted octahedron with Scheme 65. Self-assembly of metallacycles via conformational selection from various conformers [270]. a C 3 N 3 -and C 3 NO 2 -donor environment, respectively (Fig.…”
Section: Scheme 63mentioning
confidence: 99%